Spatial Analysis of the Distribution of Educational Facilities in Central Lampung Regency, Lampung Province, Indonesia - Widayanti, Tika; Sari, Ratna Mustika; Perdana, Agung Mahadi Putra (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
The rapid population growth in Central Lampung Regency has increased the demand for equitable access to educational facilities. This study aims to analyze the spatial distribution pattern of educational facilities to determine whether their placement is clustered, random, or dispersed. The analysis uses the Average Nearest Neighbor (ANN) method, a spatial analysis technique that measures the average distance between each facility and its nearest neighbor to assess spatial patterns. A total of 397 educational facilities, including junior high schools, senior high schools, and Islamic boarding schools, were analyzed using shapefile data obtained from the official geoportal of the Republic of Indonesia. The ANN results show an index value of 0.520875 with a z-score of -17.1969, indicating that educational facilities are clustered in specific regions. This clustering can lead to accessibility challenges for populations in underserved or rural areas. Therefore, it is recommended that the local government and the Central Lampung Education Office prioritize the development of new educational facilities in sparsely served districts to ensure more balanced spatial access to education services.